Paciente de sexo masculino de 44 años con hipertensión y dislipidemia - Cadena Barco, Nathaly Michelle (2020)
The present clinical case is about a young adult of 44 years old, has 2 children, is a lawyer and lives in Babahoyo, says that 5 years ago he was diagnosed with high blood pressure and takes losartan 100mg for treatment; Allergies and surgical history does not present, within the family pathological history the father is hypertensive, patient goes to routine control, does not refer symptoms, takes the medication as the doctor sends him, but does not meet diet or exercise recommendations. Vital signs: Heart rate 80 beats per minute, blood pressure 145/90mmHg, respiratory rate 18 per minute; The comprehensive nutritional assessment is performed and its BMI reflects 26.9kg / m2 overweight with increased cardiovascular risk; The corresponding laboratory tests are performed in which the results reflected hypertriglyceridemia, hypercholesterolemia and elevated LDL and in the end is diagnosed with dyslipidemia and is sent to the nutrition service for consultation. We proceed to perform the individualized nutritional intervention that will be adjusted to the socioeconomic and cultural level of the patient, the type of diet that will be prescribed will be the DASH diet, which will be divided into 4 meals a day, it is a diet used to prevent and treat hypertension arterial, is characterized by being a diet low in sodium, rich in potassium, low in saturated fat, high in fiber and together with physical activity will improve the lipid profile and blood pressure of the patient. Through the follow-up and monitoring of the patient, considerable weight loss was obtained and their biochemical tests varied favorably.